Evaluation of low‐cloud climate feedback through single‐column model equilibrium states. (30th June 2014) - Dal Gesso, S.; Siebesma, A. P.; de Roode, S. R.
Abstract : The dependency of the boundary‐layer cloud regime on the free tropospheric temperature and humidity is examined. Equilibrium state solutions obtained with the single‐column model version of the climate model EC‐EARTH are analysed in a phase space defined by the lower tropospheric stability (LTS) and a similar measure for humidity. The set‐up comprises two experiments: one with large‐scale subsidence which is constant in time and a second one with additional stochastic noise added to the subsidence. The dependency of the boundary‐layer state on the free tropospheric conditions is qualitatively consistent between the two experiments. Well‐mixed stratocumulus‐topped boundary layers are found for high LTS and moist free tropospheric conditions. Cooler and dryer free tropospheric conditions favour the presence of shallow cumulus clouds. Subsequently the response to a sea surface warming of 2 K and a free atmospheric perturbation conserving both the LTS and the relative humidity is assessed. The model predicts an overall positive low‐cloud feedback for both the constant subsidence experiment and the experiment with the additional stochastic noise.